NPCs in video games: a reflective resource for sports coaches and participant engagement - Yin, Chenxi (Frontiers in Sports and Active Living, 2024)
This perspective article explores the potential of non-player characters (NPCs) in video games as a reflective tool for coaches to enhance participant engagement in sports. While coaches traditionally focus on movement skill instruction, their role extends to fostering young people's immersion in sports contexts and potentially contribute to the possibility of lifelong participation. However, challenges persist in translating coaching theory in coach education programs into practice, including the awareness of roles and how to make young people immersion in sports. Integrating elements from video games, where NPCs play pivotal roles in shaping player experiences, presents a possible avenue for re-thinking the role of coach, especially in participation. By drawing parallels between NPCs and coaches, this article advocates for a new reflection tool for coaching roles. Future research should investigate the effectiveness of leveraging NPCs to enhance athlete engagement and motivation, ultimately creating dynamic and inclusive coaching environments that cater to the evolving needs of participants.